Neuroimaging Findings in Axenfeld-Rieger Syndrome: A Case Series - White, Samuel; Taranath, Ajay; Hanagandi, Prasad; Taranath, Deepa A.; To, Minh-Son; Souzeau, Emmanuelle; Siggs, Owen M.; Craig, Jamie E. (American Journal of Neuroradiology, 2023)
SUMMARY: Axenfeld-Rieger syndrome is an autosomal dominant condition associated with multisystemic features including developmental anomalies of the anterior segment of the eye. Single nucleotide and copy number variants in the paired-like homeodomain transcription factor 2 (PITX2) and forkhead box C1 (FOXC1) genes are associated with Axenfeld-Rieger syndrome as well as other CNS malformations. We determined the association between Axenfeld-Rieger syndrome and specific brain MR imaging neuroradiologic anomalies in cases with or without a genetic diagnosis. This case series included 8 individuals with pathogenic variants in FOXC1; 2, in PITX2; and 2 without a genetic diagnosis. The most common observation was vertebrobasilar artery dolichoectasia, with 46% prevalence. Other prevalent abnormalities included WM hyperintensities, cerebellar hypoplasia, and ventriculomegaly. Vertebrobasilar artery dolichoectasia and absent/hypoplastic olfactory bulbs were reported in >50% of individuals with FOXC1 variants compared with 0% of PITX2 variants. Notwithstanding the small sample size, neuroimaging abnormalities were more prevalent in individuals with FOXC1 variants compared those with PITX2 variants.ARSAxenfeld-Rieger syndrome